High-vacuum laser treatments enhance strength, ductility and fatigue limit of additively manufactured stainless steel - Juan Guillermo Santos Macías; Kewei Chen; Alexandre Tanguy; Nathalie Isac; Maxime Vallet; Louis Cornet; Vincent Michel; Manas Vijay Upadhyay (Materials & Design)
Post-process laser scanning under high vacuum is proposed as a non-isothermal heat treatment to simultaneously refine the intragranular microstructure near the surface and reduce surface roughness, while preventing oxidation, to enhance the mechanical response of an alloy. This treatment is performed using laser spot sizes and scan speeds that produce higher temperature gradients and faster heating/cooling rates than those encountered during manufacturing. The effectiveness of this approach is demonstrated on laser-based direct energy deposited 316L stainless steel using parameters similar to those used in laser-based powder bed fusion. High vacuum (< 0.1 Pa) lasering is conducted inside a newly integrated continuous-wave laser and scanning electron microscope (CW Laser-SEM). The treatments result in an order-of-magnitude reduction in microsegregation cell sizes (from 2.2 to 0.3 µm) coinciding with 0.3 µm-diameter dense-walled dislocation cell structures, as well as in surface roughness (from 16.6 to 0.9 µm) of LDED 316L. For a parameter set in which the laser penetrates 14% of total depth (7% each on the two widest sample surfaces), significant enhancements are obtained in yield strength (31.11%), ductility (14.2%) and fatigue limit (25%). This approach has tremendous potential to alter microstructure and improve mechanical response of additively and conventionally manufactured alloys.